Analisis Karakter Tanggung Jawab Peserta Didik Kelas III Sekolah Dasar Negeri Bayan No. 216 Surakarta pada Pembelajaran Tematik Integratif - Ajeng Wahyu Saputri; Sri Handayani; Oktiana Handini (Departement of Mathematics Education, 2023)
This study aimed to determine the character of third-grade students' responsibilities in integrated thematic learning at the State Primary School of Bayan No.216 Surakarta. This research employed a qualitative method with an analytical study approach and utilised descriptive qualitative. The subjects of this study were students and teachers in the third grade. Sources of data obtained at State Primary School of Bayan No.216 Surakarta include primary data obtained directly through questionnaires and interviews with students and teachers of the third grade. On the other hand, secondary data was collected indirectly through observation. This data was collected using interviews, observation, and questionnaires techniques. Triangulation of sources, techniques, and shorts of data analysis was used to validate data. Miles and Huberman's (2018) cycle model consists of the following steps: 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusion. Based on the data analysis, the following conclusions can be drawn: The responsibility character of third-grade students at State Primary School of Bayan No.216 Surakarta during integrative thematic learning in class was excellent, with 18 (86%) out of 21 students revealing a high level of responsibility character. On the other hand, 3 students (14%) demonstrated a low level of responsibility character.